1997
DOI: 10.1111/j.1600-0676.1997.tb00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Virological characterization and liver histology in HCV positive subjects with normal and elevated ALT levels

Abstract: LNER ISSN 0106-9543Virological characterization and liver histology in HCV positive subjects with elevated ALT levels normal and Rossini A, Ravaggi A, Agostinelli E, Bercich L, Gazzola GB, Radaeli E, Callea F, Cariani E. Virological characterization and liver histology in HCV positive subjects with normal and elevated ALT levels.Abstract: We analyzed HCV genotype and RNA titer in 36 chronically infected subjects, 20 with persistently normal or near-normal alanine aminotransferase (ALT) activity and 16 with rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Comparing the sensitivity and specificity of α-GST with viremia of these patients, we found higher sensitivity and specificity of α-GST (91.67% and 93.33% respectively) than viremia (79.17% and 88.89% respectively). This may be attributed to the intermittent pattern of viremia [30-32]. However, the sensitivity of α-GST in this group (91.67%) was lower than the sensitivity of ALT and AST which showed 100% sensitivity and higher than the sensitivity of ALP, GGT, TP, and Alb.…”
Section: Discussionmentioning
confidence: 92%
“…Comparing the sensitivity and specificity of α-GST with viremia of these patients, we found higher sensitivity and specificity of α-GST (91.67% and 93.33% respectively) than viremia (79.17% and 88.89% respectively). This may be attributed to the intermittent pattern of viremia [30-32]. However, the sensitivity of α-GST in this group (91.67%) was lower than the sensitivity of ALT and AST which showed 100% sensitivity and higher than the sensitivity of ALP, GGT, TP, and Alb.…”
Section: Discussionmentioning
confidence: 92%
“…Women are more likely to present with normal ALT, 11, 13, 56–59 but there are no significant differences in the source of HCV infection and no consistent differences in viral titre 33, 38–40, 60, 61 . Differences in HCV genotype have been reported, for example a lower frequency of genotype 1 and a higher frequency of genotype 2 in patients with normal ALT 11, 34, 37, 52, 58, 61 . However, there are no consistent findings as other studies found no difference between genotype frequency, 33, 39, 40 suggesting that epidemiological differences exert an important influence.…”
Section: Natural History Of Chronic Hepatitis C In Patients With ‘Normentioning
confidence: 90%
“…Generally, comparisons between normal ALT or elevated ALT have not identified clear differences that could be used as predictive factors of ALT level 6, 52–55 . Women are more likely to present with normal ALT, 11, 13, 56–59 but there are no significant differences in the source of HCV infection and no consistent differences in viral titre 33, 38–40, 60, 61 . Differences in HCV genotype have been reported, for example a lower frequency of genotype 1 and a higher frequency of genotype 2 in patients with normal ALT 11, 34, 37, 52, 58, 61 .…”
Section: Natural History Of Chronic Hepatitis C In Patients With ‘Normentioning
confidence: 99%
See 1 more Smart Citation